Vom ‚Vorzug theosophischer Systeme‘ - Philipp Höfele; Jan Kerkmann (Recherches Germaniques)
With Schelling’s move to Munich in 1806, one can observe his growing reception of mystical-theosophical texts, which was not least inspired by his Munich colleague and friend Franz von Baader. On the one hand Schelling clearly distances himself from the supposed immediacy of theosophical-mystical texts, since no distinction and differentiation are possible in the uninterrupted ‘mere vision’ (bloßes Schauen) of the absolute and thus no consciousness of the divine or absolute. On the other hand, however, Schelling recognizes as the ‘advantage of theosophical systems’ that there is ‘at least one nature’ in them and that they grasp the ‘abundance and depth of life’ that remains unknown to an autosufficient science. Analogously, with regard to Schopenhauer’s early philosophy of the ‘better consciousness’ (besseres Bewusstsein), it can be shown that the latter-especially in temporal proximity to Schelling’s Ages of the World-also seeks to discover a privileged way of cognizing the supersensible and the extratemporal, which transcends the subject-object correlation of ‘empirical consciousness’.